How do surgeons' trade-off between patient outcomes and risk of complications in total knee arthroplasty? a discrete choice experiment in Australia. Issue 7 (3rd July 2019) - Szawlowski, Sandie; Choong, Peter F M; Li, Jinhu; Nelson, Elizabeth; Nikpour, Mandana; Scott, Anthony; Sundararajan, Vijaya; Dowsey, Michelle M
Abstract : Objective: To measure the trade-off between risk of complications versus patient improvement in pain and function in orthopaedic surgeons' decisions about whether to undertake total knee arthroplasty (TKA). Methods: A discrete choice experiment asking surgeons to make choices between experimentally-designed scenarios describing different levels of operative risk and dimensions of pain and physical function. Variation in preferences and trade-offs according to surgeon-specific characteristics were also examined. Results: The experiment was completed by a representative sample of 333 orthopaedic surgeons (n=333): median age 52 years, 94% male, 91% fully qualified. Orthopaedic surgeons were willing to accept substantial increases in absolute risk associated with TKA surgery for greater improvements in a patient's pain and function. The maximum risk surgeons were willing to accept was 40% for reoperation and 102% for the need to seek further treatment from a general practitioner or specialist in return for a change from postoperative severe night-time pain at baseline to no night-time pain at 12 months. With a few exceptions, surgeon-specific characteristics were not associated with how much risk a surgeon is willing to accept in a patient undergoing TKA. Conclusion: This is the first study to quantify risk-benefit trade-offs among orthopaedic surgeons performing TKA, using a discrete choice experiment. This study provides insight into the risk tolerance of surgeons.